Interferones lambdas (ifnsλ) en infección con virus hepatitis C - Torres B., Claudio; Venegas S., Mauricio; Brahm B., Javier (Revista Hospital Clínico Universidad de Chile, 2011)
The current standard therapy for patients chronically infected with hepatitis C virus (HCV) is the administration of pegylated interferon-α (PEG-IFN) plus ribavirin (RBV), eliminating the virus in only about half of patients infected with the genotype most common in Chile and the world (genotype 1), being higher for genotypes 2 and 3. Genotyping of the HCV is a strong predictorof treatment response, and it defines the treatment duration (48 weeks for genotype 1 and 24 weeks for genotypes 2 and 3). Genome studies revealed the association of polymorphisms (SNPs) close to IL28B gene with increased spontaneous and treatment-inducing clearance for HCV, which are now evaluated as a strong predictor of treatment response. These SNPs are close to genes coding for type III IFNs family, known as IFNs lambda (IFNsλ), composed by IFNλ1 (IL29), IFNλ2 (IL28A) and IFNλ3 (IL28B). It has been shown that these cytokines are highly involved in antiviral immune responses, including HCV, playing IFNλ1 a central role. Today, there is an ongoing study where pegylated IFNα1 was administrated in chronic HCV patients as alternative to IFNλ therapy, seeking for a more specific response to infected hepatocytes and with fewer adverse effects.